Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Women and couples in isolated extreme environments: applications for long-duration missions - Leon, Gloria R.; Sandal, Gro Mjeldheim (Acta Astronaut, 2003)
Expedition teams provide a number of analogs relevant to crew selection for long-duration space missions. Three groups were studied that varied in team composition. Group 1 was a two woman international dyad that traversed the Antarctic continent in 97 days. Similarities in problem solving approach, respect for each other's opinions, and a collaborative process of decision making were evident. Group 2 was composed of four women, all from different countries, engaged in a six week trek across Greenland. The most important factors in overcoming interpersonal difficulties and contributing to the successful completion of the expedition were mutual respect and motivation to maintain positive and supportive relationships. Group 3 consisted of three married couples from different countries icelocked on a boat in the High Arctic for a 9 month period. The emotional support of and ability to confide in their partner were extremely important in alleviating interpersonal tensions, and contributed to the generally effective functioning of the group. Women add an element of emotional support and help to other team members that is not as evident in all-male groups. Selection of couples with strong bonds to each other is another paradigm for crew selection for extended missions.
Keywords: Antarktis; polareksspedisjoner; polarforskere; polarområdene; psykologi

Coping in Antarctica: is it possible to generalize results across settings? - Sandal, Gro Mjeldheim (Aviation Space and Environmental Medicine, 2000)
Background: To gain knowledge about psychological issues in space, data have been collected from groups in isolated and confined settings on Earth. This study examines the possibility of generalizing psychological findings across such environments. HYPOTHESIS: Psychological reactions among personnel in different Antarctic environments show similar time patterns. Antarctic personnel differ in personality from submariners to crews confined in hyperbaric chambers to military recruits. METHOD: Psychological reactions were evaluated by the Revised Antarctic Questionnaire. The Personality Characteristic Inventory was used to measure personality. RESULTS: Personnel stationed on a ship (n = 19) showed high coping during the whole mission, whereas personnel on land bases (n = 18) showed a marked decline around the third quarter. Reduced coping in the land-based groups was associated with stress from interpersonal relationships. Compared with submariners (n = 54) and hyperbaric chamber crews (n = 20), Antarctic personnel scored lower on competitiveness and higher on achievement striving. CONCLUSIONS: Similarities in physical, individual and group characteristics should be considered before extrapolating psychological findings across settings.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

The effects of personality and interpersonal relations on crew performance during space simulation studies - Sandal, Gro Mjeldheim (Life Support & Biosphere Science, 1998)
There has been a substantial increase in the number of people living and operating in isolated, confined, and artificially engineered environments, such as spacecraft, deep diving, weather stations, submarines, and polar outposts. This article gives an overview of research undertaken in a variety of extreme environments in an effort to better understand how semiautonomous, task-oriented groups operating within these environments develop over time, as well as identification of the individual characteristics that promote performance under such circumstances. Research reviewed includes space simulation studies for the European Space Agency (ESA) where groups were isolated in hyperbaric chambers, as well as findings from polar expeditions, space missions, submarine missions, and other military settings. Findings from the space simulation studies in hyperbaric chambers provided empirical evidence for interpersonal issues anecdotally reported in Antarctica and in other isolated, operational team environments, such as "scapegoating" of deviant crew members, displacement of aggression to outside personnel, and time patterns in psychological reactions. No indications of a "psychological limit" for how long people can tolerate remaining in isolation and confinement were found. Certain personality characteristics were consistently associated with coping, and individuals characterized by strong achievement motivation combined with interpersonal sensitivity seemed to adapt better than others. Together, these results have implications for selection and training of people operating within extreme environments.
Keywords: Antarktis; polarekspedisjoner; polarforskere; polarområdene; psykologi